A two years of clinical and radiographical follow up post Enucleation of Radicular Cyst (Case Report) - Mustafa, Nazih Shaban (SAS Publishers, 2023)
This case report highlights cystic lesion associated with a root tip located at the socket of previously extracted tooth which was left after extraction. In this case study we will highlight the follow up of bone healing process of 24 months duration. In addition to that the consequences of the condition which led to formation of the cystic lesion in this patient, with description of miss management leading to unfortunately unavoidable treatment which is extraction of the anterior teeth. Frequent assessment of the patient clinically and radiographically after the surgical removal of the cystic lesion have been done for 2 years duration. In conclusion this young patient could be treated in other way to prevent the teeth extraction and to avoid surgery.